Hybrid kernel search and particle swarm optimization with Cauchy perturbation for economic emission load dispatch with valve point effect - Dong, Ruyi; Ma, Long; Chen, Huiling; Heidari, Ali Asghar; Liang, Guoxi (Frontiers in Energy Research, 2023)
Due to the growing concern over environmental protection, economic and environmental power dispatching has become a hot topic in the field of power system control. In essence, it is multi-objective optimization that minimizes fuel costs and emission pollution without violating the operational constraints. To solve this problem, the MOP is decomposed into individual objects by weighted sum method and Newton's method is used to tackle the equation constraints iteratively. Moreover, a hybrid algorithm (HKSOPSO-CP) based on kernel search optimization (KSO) and Particle swarm optimization (PSO) with Cauchy perturbation is proposed in this paper. The proposed HKSOPSO-CP optimization algorithm are employed to solve IEEE 6-unit, 10－unit and 40-unit Economic Emission Dispatch (EED) problem. The results display that the proposed HKSOPSO-CP algorithm for EED problem can acquire a better trade-off between fuel cost and emission objectives compared to those reported algorithms in the recent literature.